A review of the genus Paraleptomenes Giordani Soika, 1970 (Hymenoptera: Vespidae: Eumeninae: Odynerini) from the Indian subcontinent,with the description of a new species from the eastern Himalayas - Kumar, Girish P.; Carpenter, James M.; Sharma, Gaurav (Zootaxa, 2014)
The genus Paraleptomenes Giordani Soika, 1970 is reviewed for the Indian subcontinent. A new species Paraleptomenes darugiriensis Kumar, Carpenter & Sharma, sp. nov. is described. The male of P. rufoniger Giordani Soika, 1994 is described for the first time. The distribution records of P. humbertianus (de Saussure, 1867), P. miniatus mephitis (Cameron, 1901), P. miniatus miniatus (de Saussure, 1855), and P. rufoniger Giordani Soika, 1994 in the Indian states are augmented. A key to species of the Indian subcontinent and a world checklist of species are provided.